INVESTIGATION OF NATURAL EXTRACTS AS GREEN CORROSION INHIBITORS IN STEEL USING DENSITY FUNCTIONAL THEORY - Muhamad Akrom (Jurnal Teori dan Aplikasi Fisika, 2022)
One of the materials with low corrosion resistance is steel when it interacts with a corrosive environment. The use of green inhibitors is able to provide good corrosion inhibition performance with high inhibition efficiency on steel. Green inhibitors which in their compound structure contain heteroatom groups (such as O, N, S, P) and aromatic rings are efficiently used as corrosion inhibitors in steel. This paper provides an important comparative overview for the development of green inhibitors of natural extracts in steel. The study of DFT at the atomic level based on molecular orbitals, chemical quantum parameters, and adsorption characteristics showed results that were in accordance with experimental results. The distribution of electron density through the Frontier Molecular Orbitals (FMO) plot illustrates the prediction of active sites through the distribution of the HOMO-LUMO region of inhibitor molecules that interact with the steel surface. To get the correlation between the electronic properties of the inhibitor molecule and the corrosion inhibition potential, calculate the quantum chemical parameters such as ionization potential (I), electron affinity (A), global hardness (?), absolute electronegativity (?), global softness (?) , the transferred electron fraction (?N), global electrophilicity (?) and electron return donation (?Eback-donation) indicate the reactivity of inhibitor molecules which have excellent potential to interact and bind strongly to metal surfaces, thus potentially producing high inhibitory efficiency. The mechanism of corrosion inhibition can be through chemical adsorption and/or physical adsorption by forming a complex compound between the inhibitor molecule and the steel surface to protect it from the corrosive environment. The development of future studies should be able to display the mechanism of interaction and inhibition of inhibitor molecules in more detail and systematically at the atomic level on several metal surfaces such as Fe, Al, Cu, and others.